THE USE OF THE VERB REPRESENTING PRAISE IN THE HOLY QUR’AN - Akhrorov Ivadulla Ziyatovich UzKHIA (Galaxy International Interdisciplinary Research Journal, 2021)
The Qur’an describes several ways to praise and rebuke. Praise is an Arabic word and is used in the sense of praising, complimenting, and elevating. One of the forms of praise in the Qur’an comes with the verb “ نِعْ مَ ” (ne’ ma). This verb is used in the sense of “how nice, how worthy, how good”.